Determination of the statistical power in yield experiments in corn - Vargas-Rojas, Jorge Claudio; García, Fernando (Revista Mexicana de Ciencias Agrícolas, 2022)
Prospective analysis of the statistical power of a hypothesis test should be one of the most important stages of any experiment; however, it is frequently omitted. In particular, for Costa Rica, no studies related to this topic were found for yield experiments in corn cultivation. The objective of this work was to determine the statistical power of a completely randomized design for yield experiments in the cultivation of corn (Zea mays) by simulating uniformity trials. To perform the calculations of power, the parameters of the spatial correlation process of a uniformity trial established in Santa Cruz, Costa Rica in 2018 were estimated. These estimates were used to perform 10 000 simulations of larger random fields, which allowed overlapping different number of repetitions and estimate the statistical power to detect a difference of 10% with respect to the mean in an experiment with a completely randomized design at a significance level of 5%. The 80% power was obtained with eight repetitions and it is concluded that, under the experimental conditions of this work, in yield trials in the cultivation of corn, to detect a difference of means of 10% at a level of significance 5%, eight or more repetitions should be used.
Keywords: blank test; geostatistical simulations; number of repetitions; random fields; test power